FEATURES OF THE DEVELOPMENT PROGRAM OF VOLGOGRAD STATE TECHNICAL UNIVERSITY - FLAGSHIP UNIVERSITY OF VOLGOGRAD REGION - Alexander V. Navrotskiy (Высшее образование в России)
The article considers the main areas of development of Volgograd State Technical University as the supporting university of Volgograd region. The mission, the strategic goal, and objectives of the flagship university are presented. The characteristics of high quality breakthroughs in the field of educational and scientific activities, in the creation of a favorable business environment of the university are given. The author outlines the positive consequences and the prospects of the realization of the VSTU development program for the socio-economic situation in Volgograd region.